Telemedicine in pediatric rheumatology: this is the time for the community to embrace a new way of clinical practice - Susan Shenoi; Kristen Hayward; Megan L. Curran; Elizabeth Kessler; Jay J. Mehta; Meredith P. Riebschleger; Helen E. Foster (BMC, 2020)
Abstract Background The use of telemedicine in pediatric rheumatology has been historically low. The current COVID 19 global pandemic has forced a paradigm shift with many centers rapidly adopting virtual visits to conduct care resulting in rapid expansion of use of telemedicine amongst practices. Body This commentary discusses practical tips for physicians including guidance around administrative and governance issues, preparation for telemedicine, involving the multidisciplinary care team, and teaching considerations. We also outline a standard proforma and smart phrases for the electronic health record. A proposed variation of the validated pediatric gait arms legs spine examination (pGALS) called the video pGALS (VpGALS) as a means of conducting virtual pediatric rheumatology physical examination is presented. Conclusion This commentary provides a starting framework for telemedicine use in pediatric rheumatology and further work on validation and acceptability is needed.